2009
DOI: 10.1080/02841850903085576
|View full text |Cite
|
Sign up to set email alerts
|

Bolus compared with continuous infusion of microbubble contrast agent using real-time contrast harmonic imaging ultrasound in breast tumors

Abstract: CEUS using real-time harmonic imaging in order to evaluate breast tumors should be performed with bolus administration of contrast agent in order to achieve better intensity/time curve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…For microbubble, this administration approach is also better for achieving the ideal ultrasound contrast-enhanced imaging of tumor compared with the continuous infusion [40]. In addition, it also permitted convenient observation of the response to microbubble injection in mice, since no anesthetization was performed during the experiment.…”
Section: Discussionmentioning
confidence: 97%
“…For microbubble, this administration approach is also better for achieving the ideal ultrasound contrast-enhanced imaging of tumor compared with the continuous infusion [40]. In addition, it also permitted convenient observation of the response to microbubble injection in mice, since no anesthetization was performed during the experiment.…”
Section: Discussionmentioning
confidence: 97%
“…After contrast agent injection, bubbles flushed in and out of malignant lesions faster than of benign lesions. Peak enhancement density is higher in malignant lesions [23][24]. The good correlation with MRI results has indicated that quantitative assessment is reliable [25][27].…”
Section: Introductionmentioning
confidence: 83%
“…Evaluating time-intensity curves clear cut-off values have demonstrated that the bolus injection is the method of choice (14). But there is still a need for comparative studies in order to identify the correct injected dose.…”
Section: Discussionmentioning
confidence: 99%